Research progress of circRNA as a biomarker of osteoporosis - Du, Xing; Chen, Zhongyao; Shui, Wei (Frontiers in Genetics, 2024)
Osteoporosis, as a chronic metabolic bone disease, has the characteristic of insidious disease progression, which often leads to relatively delayed disease diagnosis. Therefore, early screening for osteoporosis has become a major public health challenge. The latest research indicates that circRNA is widely involved in the regulation of bone metabolism and is closely related to the occurrence and development of osteoporosis. Based on its high degree of sequence conservation and stability, circRNA has the potential to become a new clinical biomarker. The study of biomarkers is generally based on body fluid samples or adjacent tissue samples, with blood being the most commonly used, which can be divided into sources such as serum, plasma, peripheral blood monocytes, and plasma exosomes. Therefore, this article aims to review the research status of circRNA as a biomarker of osteoporosis.